Zinc ion battery solid electrolyte and preparation and application thereof

The zinc-based supramolecular crystals are formed by self-assembly of nitrile organic molecules and organic zinc salts, which solves the problem of low ion conductivity of solid electrolytes in existing zinc ion batteries, and achieves efficient transmission of zinc ions and improved battery performance.

CN119518070APending Publication Date: 2025-02-25CHINA NAT PETROLEUM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311081506.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing zinc ion batteries have low ion conductivity and poor transmission performance of zinc ions, making it difficult to achieve high-efficiency and rapid transmission at low temperatures.

Method used

Using nitrile organic molecules and organic zinc salts as main materials, they are self-assembled into zinc-based supramolecular crystals by heating and melting and standing at room temperature to form a structure with a three-dimensional ion transport channel.

Benefits of technology

It significantly improves the diffusion and transmission performance of zinc ions, improves the ion conductivity and ion migration of solid electrolytes, extends the cycle life of the battery, and increases the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518070A_ABST
    Figure CN119518070A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte of a zinc ion battery, which is self-assembled into a zinc-based supramolecular crystal by taking nitrile organic molecules and organic zinc salt as main materials. The invention also discloses a preparation method and application thereof. According to the zinc ion battery solid electrolyte provided by the embodiment of the invention, the ionic conductivity and the ionic transference number of the solid electrolyte can be improved, the electrochemical stability window of the solid electrolyte is improved, the compatibility of the solid electrolyte and an electrode is enhanced, and the reversibility, the utilization rate and the cycle life of a positive electrode and a negative electrode are improved, so that the energy density of the whole battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a zinc ion solid electrolyte and a preparation method and application thereof. Background Art

[0002] Zinc-ion batteries (ZIBs) are usually paired with aqueous electrolytes, which can lead to severe dendrites and side reactions (such as hydrogen evolution, corrosion, and passivation) at the zinc anode, limiting the further development of zinc batteries. In order to alleviate the above problems, many strategies have been explored, including "salt-in-water", molten salt or hydrogel electrolytes. However, the above strategies can only suppress hydrogen evolution and passivation at the anode to a certain extent but cannot eliminate them, and these measures are costly and cumbersome to prepare.

[0003] Solid electrolytes (SEs) are expected to solve the problems that plague ZIBs due to their liquid-free properties, high stability, and high safety. Currently, most SEs used in ZIBs are solid polymer electrolytes (SPEs) composed of salt and polymer matrices. However, Zn in SPEs 2+ The transport of ions depends mainly on the thermal motion of polymer chains, so their transport kinetics are very slow. Their ionic conductivity is very low (about 10 -5 S cm -1 , 25°C), and their Zn 2+ Migration number (t Zn 2+ ) is less than 0.3, indicating poor ion transport performance. Conventional ceramic electrolytes based on ion transition mechanisms seem to be an option, but the ionic conductivity of zinc-based ceramics at high temperatures is also not ideal. Due to the high charge density of zinc ions and their strong chemical bonding with the host medium, divalent zinc ions have poor mobility in typical ceramic SEs, especially at room temperature. Therefore, the development of new SE materials other than traditional ceramic or polymer hosts to achieve efficient and rapid transport of zinc ions at low temperatures has become a focus of industry research. Summary of the invention

[0004] In order to achieve ultra-high Zn in solid electrolytes for Zn-ion batteries 2+ Conductivity, making the present invention.

[0005] As one aspect of the present invention, it relates to a solid electrolyte for zinc ion batteries, which uses nitrile organic molecules and organic zinc salts as main materials and self-assembles into zinc-based supramolecular crystals.

[0006] In a specific embodiment, the nitrile organic molecule is succinonitrile (SN).

[0007] In a specific embodiment, the organic zinc salt refers to zinc bis(trifluoromethylsulfonyl)imide (Zn(TFSI)2).

[0008] As another aspect of the present invention, it relates to a method for preparing the above-mentioned zinc ion battery solid electrolyte, comprising:

[0009] 1) heating and melting the organic zinc salt and the nitrile organic molecules;

[0010] 2) Allow to stand at room temperature to obtain Zn-based supramolecular crystals.

[0011] In a specific embodiment, in step 2), the nitrile organic molecule is succinonitrile (SN), and the organic zinc salt is zinc bis(trifluoromethylsulfonyl)imide (Zn(TFSI)2);

[0012] In a specific embodiment, in step 2), the molar ratio of the organic zinc salt to the nitrile organic molecule is from 1:6 to 1:3, the heating temperature is 65-80° C., and the reaction time is 1-3 h.

[0013] The nitrile organic molecule and the organic zinc salt are preferably dried before use to remove any moisture therein.

[0014] As another aspect of the present invention, it relates to a zinc ion battery, which uses the above zinc ion battery solid electrolyte as electrolyte.

[0015] In a specific embodiment, the zinc ion battery uses metal zinc foil as the negative electrode; the positive electrode uses a mixed slurry of tetrachloro-1,4-benzoquinone, PVDF, carbon black and ZMCs coated on a carbon cloth current collector.

[0016] The solid electrolyte for zinc ion batteries provided by the embodiments of the present invention can improve the ionic conductivity and ion migration number of the solid electrolyte, improve its electrochemical stability window, enhance the compatibility of the solid electrolyte with the electrode, and improve the reversibility, utilization rate, and cycle life of the positive and negative electrodes, thereby improving the energy density of the whole battery. The nitrile functional group can be complexed with Lewis acidic metals, so it can self-assemble with zinc ions to form a supramolecular structure, construct an ordered three-dimensional ion tunnel, and enhance the diffusion of zinc ions. Molecular dynamics simulations have confirmed that the ordered lattice accurately regulates the three-dimensional (3D) ion transport channel, greatly promoting the Zn in SE through the ion hopping mechanism. 2+ In supramolecular crystals, anions are firmly bound in the lattice, so there is no anion migration. This type of molecular crystal has the typical characteristics of a single ion conductor, that is, only the corresponding cations (zinc ions) migrate, which can reduce electrode polarization and improve the utilization of positive and negative electrodes. These new ZMCs exhibit high ionic conductivity over a wide temperature range and have a single Zn 2+The characteristics of the Zn metal battery transmission promote highly reversible Zn plating / stripping without forming dendrites or HER. In addition, the low temperature resistance and fast charging performance of batteries based on this type of solid electrolyte are also improved. Since nitrile organic molecules have small molecule characteristics, they are different from inorganic ceramics and solid polymer electrolytes. They are naturally more compatible with positive and negative electrodes, which also improves the interface problems of solid electrolytes. Considering the intrinsic safety of zinc metal batteries, this invention has broad application prospects in portable and fixed energy storage and power supply equipment in oil and gas fields with strict safety requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The solid electrolyte crystal structure corresponding to Example 4 has a three-dimensional ion transport tunnel.

[0018] Figure 2 : Schematic diagram of the solid electrolyte structure of an embodiment of the present invention. DETAILED DESCRIPTION

[0019] In view of the low ionic conductivity of the existing solid electrolyte (SE) and the 2+ The inventors found that the defects of the prior art can be overcome by preparing supramolecular crystals (MC). Supramolecular crystals (MC) can promote Zn 2+ Fast transfer.

[0020] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0021] The technical effects of the present invention are further explained below in conjunction with specific embodiments and test characterizations.

[0022] Succinonitrile and tetrachloro-1,4-benzoquinone (C14Q) can be purchased from Aladin, and bis(trifluoromethanesulfonic acid)imide zinc can be purchased from Energy Chemical. The nitrile organic molecules and the organic zinc salt should be dried before adding them into the reaction.

[0023] Example 1

[0024] Succinonitrile was used as the solid electrolyte matrix, zinc bis(trifluoromethanesulfonic acid)imide was used as the zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 6:1, and the mixture was heated and stirred at 65°C to dissolve each other. After cooling, it was allowed to stand for 1 day and self-assembled into zinc-based supramolecular crystals, which were recorded as solid electrolyte ZMC-6 / 1.

[0025] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZMC-6 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0026] Example 2

[0027] Succinonitrile was used as the solid electrolyte matrix, zinc bis(trifluoromethanesulfonic acid)imide was used as the zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 5:1, and they were mutually dissolved after heating and stirring at 65°C. After cooling and standing for 1 day, they self-assembled into zinc-based supramolecular crystals, which were recorded as solid electrolyte ZMC-5 / 1.

[0028] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZMC-5 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0029] Example 3

[0030] Succinonitrile was used as the solid electrolyte matrix, zinc bis(trifluoromethanesulfonic acid)imide was used as the zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 4:1, and they were mutually dissolved after heating and stirring at 65°C. After cooling and standing for 1 day, they self-assembled into zinc-based supramolecular crystals, which were recorded as solid electrolyte ZMC-4 / 1.

[0031] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZMC-4 / 1 = 6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0032] Example 4

[0033] Succinonitrile was used as the solid electrolyte matrix, bis(trifluoromethanesulfonic acid)imide zinc was used as the zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 3:1, and they were mutually dissolved after heating and stirring at 65°C, and then allowed to stand for 1 day after cooling, and self-assembled into zinc-based supramolecular crystals, which were recorded as solid electrolyte ZMC-3 / 1. The crystal structure is shown in the figure below. Figure 1 As shown in the optical microscope morphology Figure 2 shown.

[0034] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZMC-3 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0035] Example 5

[0036] Adiponitrile was used as the solid electrolyte matrix, zinc bis(trifluoromethanesulfonic acid)imide was used as the zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 3:1, and they were mutually dissolved after heating and stirring at 65°C, and then allowed to stand for 1 day after cooling, and self-assembled into zinc-based supramolecular crystals, which were recorded as solid electrolyte adiponitrile-based molecular crystals (ZAC-3 / 1).

[0037] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZAC-3 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0038] Example 6

[0039] Succinonitrile was used as the solid electrolyte matrix, zinc trifluoromethanesulfonate was used as the zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 3:1, and they were mutually dissolved after heating and stirring at 65°C, and then allowed to stand for 1 day after cooling, and self-assembled into zinc-based supramolecular crystals, which were recorded as solid electrolyte zinc trifluoromethanesulfonate-based molecular crystals (ZSC-3 / 1).

[0040] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZSC-3 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0041] Comparative Example 1

[0042] Imidazole was used as a solid electrolyte matrix, zinc bis(trifluoromethanesulfonic acid)imide was used as a zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 3:1, the mixture was heated and stirred at 65°C, and then allowed to stand for 1 day after cooling to form an imidazole-based solid electrolyte (ZIC-3 / 1).

[0043] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZIC-3 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0044] Comparative Example 2

[0045] Succinonitrile was used as the solid electrolyte matrix, zinc sulfate was used as the zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 3:1, the mixture was heated and stirred at 65°C, and then allowed to stand for 1 day after cooling to form a zinc sulfate-based solid electrolyte (ZSUC-3 / 1).

[0046] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZSUC-3 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0047] Comparative Example 3

[0048] Succinonitrile was used as a solid electrolyte matrix, zinc bis(trifluoromethanesulfonic acid)imide was used as a zinc salt, the molar ratio of the electrolyte matrix to the zinc salt was 3:1, the mixture was heated and stirred at 45°C, cooled and allowed to stand for 1 day to form a solid electrolyte (ZMCL-3 / 1).

[0049] A button battery was prepared using tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZMCL-3 / 1=6:1:2:1 as the positive electrode material, carbon cloth as the current collector, and zinc foil with a thickness of 0.05 mm as the negative electrode.

[0050] Performance Testing

[0051] The solid electrolyte materials prepared in Examples 1-6 and Comparative Examples 1-3 were tested for room temperature ion conductivity, ion migration number, and button cell cycle number.

[0052] The room temperature ionic conductivity test is as follows: using stainless steel foil as positive and negative electrodes, the solid electrolytes prepared in Examples 1-6 and Comparative Examples 1-3 as electrolytes, assembling button-type symmetrical batteries, and testing with a blue electric test system.

[0053] The ion migration number test is as follows: zinc foil is used as the positive and negative electrodes, the solid electrolyte prepared in Examples 1-6 and Comparative Examples 1-3 is used as the electrolyte, button-type symmetrical batteries are assembled, and the test is performed using a blue electric test system.

[0054] Button battery cycle test: Tetrachloro-1,4-benzoquinone (C14Q): polytetrafluoroethylene (PTFE): carbon black: ZMCs = 6:1:2:1 as the positive electrode material, zinc foil negative electrode, and the solid electrolyte prepared in Examples 1-6 and Comparative Examples 1-3 as the electrolyte, assemble button batteries, and test with the Blue Electric test system.

[0055] Table 1

[0056] <![CDATA[Room temperature ionic conductivity Scm -1 > Ion migration number Button battery cycle times Example 1 <![CDATA[3.31×10 -5 ]]> 0.35 1000 Example 2 <![CDATA[6.26×10 -5 ]]> 0.41 1000 Example 3 <![CDATA[3.95×10 -4 ]]> 0.63 1000 Example 4 <![CDATA[6.02×10 -4 ]]> 0.97 2000 Example 5 <![CDATA[4.73×10 -5 ]]> 0.54 1000 Example 6 <![CDATA[1.19×10 -4 ]]> 0.48 1000 Comparative Example 1 <![CDATA[8.37×10 -6 ]]> 0.44 500 Comparative Example 2 <![CDATA[1.06×10 -8 ]]> 0.23 20 Comparative Example 3 <![CDATA[1.12×10 -5 ]]> 0.37 200

[0057] As can be seen from Table 1, the solid electrolytes prepared in Examples 1-6 have a crystal structure with three-dimensional regular ion channels, and the diffusion and transport performance of zinc ions is significantly improved, thereby improving the ionic conductivity, ion migration number and cycle life of the corresponding electrolytes.

[0058] Comparative Example 1 changes the matrix used, resulting in the failure to form a regular ion transport channel. Compared with Example 4, both the ion mobility and the ion migration number are reduced, thereby weakening the cycle life.

[0059] Comparative Example 2 changed the zinc salt used, resulting in the failure to form a regular ion transport channel. Compared with Example 4, both the ion mobility and the ion migration number were reduced, thereby weakening the cycle life.

[0060] Comparative Example 3 changed the temperature of material preparation, resulting in the failure to form a regular ion transport channel. Compared with Example 4, both the ion mobility and the ion migration number were reduced, thereby weakening the cycle life.

[0061] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0062] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A zinc ion battery solid electrolyte, characterized in that Taking nitrile organic molecules and organic zinc salts as the main materials, they self-assemble into zinc-based supramolecular crystals.

2. The zinc ion battery solid electrolyte according to claim 1, characterized in that The nitrile organic molecule is succinonitrile.

3. The zinc ion battery solid electrolyte according to claim 1, characterized in that The organic zinc salt refers to zinc bis(trifluoromethylsulfonyl)imide.

4. A method for preparing a zinc ion battery solid electrolyte according to any one of claims 1 to 3, characterized in that: include: 1) heating and melting the organic zinc salt and the nitrile organic molecules; 2) Allow to stand at room temperature to obtain Zn-based supramolecular crystals.

5. The method according to claim 4, characterized in that In step 1), the nitrile organic molecule is succinonitrile, and the organic zinc salt is bis(trifluoromethylsulfonyl)imide zinc; 6. The method according to claim 5, characterized in that In step 1), the molar ratio of the organic zinc salt to the nitrile organic molecule is from 1:6 to 1:

3.

7. The method of claim 5, characterized in that In step 1), the heating is performed at 65-80° C. for 1-3 h.

8. The method of claim 5, characterized in that The nitrile organic molecule and the organic zinc salt should be dried before adding into step 1).

9. A zinc ion battery, characterized in that: The zinc ion battery solid electrolyte according to any one of claims 1 to 3 is used as the electrolyte.

10. The zinc ion battery according to claim 9, characterized in that: The negative electrode uses metal zinc foil as the negative electrode; the positive electrode uses a mixed slurry of tetrachloro-1,4-benzoquinone, PVDF, carbon black and ZMCs coated on a carbon cloth current collector.